A E-learning in the Digital Era: Advantages, Challenges and Successful Implementation Strategies - Arla, Arla Salfa ((JELE) Journal Of English Language and Education, 2024)
This study investigates the paradigm of "E-learning in the Digital Era: Advantages, Challenges, and Successful Implementation Strategies." Surveying 88 participants, the research explores gender distribution, age demographics, and preferences in E-learning. The survey highlights challenges such as technical issues and engagement while underscoring the positive impact on knowledge retention. The findings contribute valuable insights into the nuances of digital education, guiding the development of strategies to enhance E-learning experiences.